Using gene carrier probability to select high risk families for identifying germline mutations in breast cancer susceptibility genes. Issue 2 (February 1998) - Chang-Claude, J; Dong, J; Schmidt, S; Shayeghi, M; Komitowski, D; Becher, H; Stratton, M R; Royer-Pokora, B
Abstract : Germline mutations in highly penetrant autosomal dominant genes explain about 5% of all breast cancer, and heritable mutations in the BRCA1 breast and ovarian cancer susceptibility gene account for 2-3% of breast cancer in the general population. Nevertheless, the presence of such mutations is highly predictive of disease development. Since screening for mutations is still technically laborious, we investigated whether the prior probability of being a carrier of a dominant breast cancer susceptibility gene in the youngest affected family member could be used to identify families in which the probability of finding a mutation is sufficiently high. Sixty German families with three or more cases of breast/ovarian cancer with at least two cases diagnosed under the age of 60 were screened for mutations by SSCP/CSGE and subsequent direct sequencing. Thirteen germline truncating/splicing mutations in BRCA1 were found in 33% (6/18) of the breast-ovarian cancer families and in 17% (7/42) of breast cancer only families. All the families showing mutations in BRCA1 had carrier probabilities of 0.65 or higher. In families with prior carrier probabilities above 0.6, the proportion detected was 0.46 in breast-ovarian cancer families and 0.26 in breast cancer only families. The average age at diagnosis of breast or ovarian cancer in families with BRCA1 mutations was 41.9 years and significantly lower than in families without mutations (p < 0.05). Mutation carriers and obligate carriers were also found to have cancers at other sites. The probability of being a susceptibility gene carrier, taking into account the complete pedigree information, allows uniform characterisation of all types of families for identifying those in which mutation analysis for BRCA1/2 is warranted. However, prior probabilities calculated using this method can be reduced when the correlation between genotype and phenotype is imperfect. A larger series of families needs to be investigated in this fashion to provide better estimates of the detection rate for different ranges of carrier probabilities.